The world rubber economy : - Grilli, Enzo R. (Published for the World Bank [by] the Johns Hopkins University Press, 1980)
In order to put in perspective some of the choices that natural rubber producing countries will have to make, this study assesses the magnitude and scope of the changes that have recently occurred in the rubber economy throughout the world and the likely consequences of these changes on the future of the world natural rubber industry.